Analysis of glamorous acquisitions in the telecommunications sector: Overvaluation or success? - Julio Navío-Marco; Silvia Serrano Calle; Marta Solórzano-García (International Telecommunications Society (ITS), 2017)
This article analyses the performance and value creation of the glamorous operations of mergers and acquisitions (M&A) in the telecommunications sector, trying to understand if the glamour companys M&A operations conduct to the stockholder wealth maximization, and the role of acquirers characteristics and its behaviour as glamour firm. After calculating the abnormal returns of telecommunications M&A from 2000 to 2010 and evaluating the value creation/destruction of these operations, we conclude that glamour tends to be opposite to value creation in the long run. The glamour firms show significant value destruction in certain timeframes and worse performance than non-glamour firms. From our analysis, it is evident that certain acquirers characteristics, such as size, are determinant in the glamour behavior. Related to this, the influence of the intangible assets (and particularly the intangible ratio) is a new contribution from this analysis.
Keywords: G34; L96; 330; Mergers and Acquisitions; Glamorous Acquisitions; Strategy; Value creation; Telecommunications